The development of frustration tolerance and arbitrary emotion regulation in the educational process - Malyar, Olena; Bozhok, Natalia (My University, 2014)
In the article the theoretical analysis of problems of arbitrary emotional regulation and frustration tolerance of individual is conducted. The main approaches to the understanding of terms «arbitrary emotion regulation», «frustration» and «frustration tolerance» are considered and the influence of the mentioned terms on the emotional sphere of individual is defined.
Keywords: особистість; емоційна довільність; фрустраційна толерантність; фрустрація; фрустрационная толерантность; фрустрация; личность; эмоциональная произвольность; frustration; frustration tolerance; individual; arbitrary emotional regulation; кафедра ділової іноземної мови та міжнародної комунікації